Dichotomy between in-plane magnetic susceptibility and resistivity anisotropies in extremely strained BaFe2As2 - Mingquan He (Nature Portfolio, 2017)
Interplay between lattice, orbital, magnetic and nematic degrees of freedom is crucial for the superconductivity in Fe-based materials. Here, the authors demonstrate the subdominant roles of pure lattice distortions and/or orbital ordering in BaFe2As2 by characterizing the in-plane magnetic susceptibility anisotropy.